An fMRI-Neuronavigated Chronometric TMS Investigation of V5 and Intraparietal Cortex in Motion Driven Attention - Alexander, Bonnie; Laycock, Robin; Crewther, David P.; Crewther, Sheila G. (Frontiers in Human Neuroscience, 2018)
The timing of networked brain activity subserving motion-driven attention in humans is currently unclear. Functional MRI (fMRI)-neuronavigated chronometric transcranial magnetic stimulation (TMS) was used to investigate critical times of parietal cortex involvement in motion-driven attention. In particular, we were interested in the relative critical times for two intraparietal sulcus (IPS) sites in comparison to that previously identified for motion processing in area V5, and to explore potential earlier times of involvement. fMRI was used to individually localise V5 and middle and posterior intraparietal sulcus (mIPS; pIPS) areas active for a motion-driven attention task, prior to TMS neuronavigation. Paired-pulse TMS was applied during performance of the same task at stimulus onset asynchronies (SOAs) ranging from 0-180 ms. There were no statistically significant decreases in performance accuracy for trials where TMS was applied to V5 at any SOA, though stimulation intensity was lower for this site than for the parietal sites. For TMS applied to mIPS, there was a trend toward a relative decrease in performance accuracy at the 150 ms SOA, as well as a relative increase at 180 ms. There was no statistically significant effect overall of TMS applied to pIPS, however there appeared a potential trend toward a decrease in performance at the 0 ms SOA. Overall, these results provide some patterns of potential theoretical interest to follow up in future studies.